Income Smoothing, Default Risk and Stock Price Crashes: The Moderating Effect of Manager Age - Butar-Butar, Sansaloni (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this study is to investigate the moderating role of manager age on the association between income smoothing and stock price crashes and the association between default risk and stock price crashes. The data was collected from the samples of 182 companies firms listed on the Indonesia Stock Exchange from 2013 to 2017 (910 firm-year observation). Using the multivariate analysis as the data analysis method, this study revealed that manager age and default risk were negatively associated with stock price crashes. On the other hand, the income smoothing was not significantly associated with stock price crashes. With regard to moderating effect of manager age, the results showed that manager age effect the association between default risk and stock price crashes with a positive direction. Meanwhile, no significant effect of manager age on the association between income smoothing and stock price crashes is found in this study.